Three‐dimensional structural‐material models of the formation of the Nyurbinskaya and Botuobinskaya kimberlite pipes (Yakutian Diamondiferous Province, Russia) - E. V. Serebryakov; A. S. Gladkov; D. A. Koshkarev (Геодинамика и тектонофизика, 2019)
The Nyurbinskaya and Botuobinskaya kimberlitic pipes were in the focus of a comprehensive study aimed to investigate their structural and material positions as the main deposits in the Nakyn field (Yakutian Diamondife‐ rous Province, Russia). This paper present the study results and 3D structural‐material models showing the formation of these deposits. In application to geological studies, the 3D modeling technologies allow taking into account the ani‐ sotropy of material complexes comprising kimberlite pipes, as well as inconsistencies in the structural and morpho‐ logical properties of ore‐bearing structures. In order to discover the structural positions and features of the fault‐ block structures of the deposits, tectonophysical methods were used in combination with tacheometric surveys. Based on this more comprehensive and integrated approach, the existing fault patterns were clarified in detail; elements of the internal fault structure were mapped; fault azimuths and dip angles were estimated; and thickness values were obtained. Computer processed data were used to construct 3D models showing the fault‐block structures of the Nyurbinskaya and Botuobinskaya pipes. The mineralogical, petrographic and diamond‐bearing features of various kimberlite generations comprising these pipes were investigated in order to reconstruct the morphology and spatial positions of each of the selected complexes in the current cross‐section and in accordance with intrusion phases. The 3D frame models of geological bodies were constructed for all the magmatic phases, including porphyry kimberlite and eruptive and autolithic kimberlite breccia. The structural‐material models for the Nyurbinskaya and Botuobin‐ skaya pipes were based on a synthesis of their material and structural features discovered in the previous stages of the study. The models presented in this paper are used to discuss temporal relationships between faults in the kim‐ berlitic structure and material complexes comprising the pipes. The models show that the pipes occurred in the near‐ surface structures of shear tension, which developed in the areas where the NNE‐striking fault was conjugated with the ENE‐ and NE‐striking faults in the fault zone resulting from several stage of the tectono‐magmatic activity. In this case, the kimberlite melt material was transported in discrete portions from the source through deep‐seated faults, and the faults acted as channels characterized by an increased permeability. Disjunctive elements identified in this study facilitated magma movements and localization of kimberlite bodies.